TEKNIK PEMBENIHAN IKAN KOI (CYPRINUS CARPIO) DENGAN RASIO JANTAN BETINA YANG BERBEDA - NURMAHRAINI, NURMAHRAINI; RAHMADANI, THOY BATUN CITRA (GANEC SWARA, 2024)
Koi fish is a type of freshwater ornamental fish that has great demand. This commodity has become valuable in some regions in Indonesia. One of the problem in koi fish is producing good quality larvae. Therefore, it is necessary to make observation regarding the use of broodstock. This research aims to see the best ratio between male and female in producing koi fish larvae. The result showed that spawning using male to female ratio 1:2 was better than 1:3. It can be seen from the hatching rate of 1:2 and 1:3, 51% and 26%, respectively. The growth of koi fish larvae within 2 weeks reached a size 2,80 cm. The water quality during the research showed in optimum condition and can support for the life of fish koi